Improving the Sensory, Nutritional and Technological Profile of Conventional and Gluten-Free Pasta and Bakery Products - Simonato, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Cereal-based products such as pasta and baked goods represent staple foods for human nutrition. Due to their worldwide diffusion, these products can be carriers of nutrients and bioactive compounds; therefore, they lend themselves very well to the fortification process. Furthermore, among new formulations of cereal-based food, gluten-free products have become popular even among people without celiac disease who have chosen a gluten-free lifestyle. The improvement of well-being, sustainable lifestyles, and waste control are also aims of the United Nations for the Agenda 2030, which has motivated food scientists and industrial producers to research new and healthier formulations for pasta and baked goods preparations. In this context, researchers are also encouraged to use agro-industrial by-products of high added value for food fortification. The Special Issue "Improving the Sensory, Nutritional and Technological Profile of Conventional and Gluten-Free Pasta and Bakery Products" collected ten original articles focused on new types of gluten-free pasta or baked product formulations as well as agro-industrial by-product utilization. The final aim was the preparation of valuable products from a nutritional, technological, and sensory viewpoint.